EFEKTIFKAH RESTORATIF JUSTICE ? SUATU KAJIAN UPAYA OPTIMALISASI SISTEM PERADILAN PIDANA DI INDONESIA - L. Alfies Sihombing; Yeni Nuraeni (Universitas Suryakancana, 2023)
The criminal justice system in any country has an important role in upholding law and order, ensuring justice for victims, and facilitating rehabilitation for offenders. Recently, there has been an increasing awareness that the conventional punitive approach to criminal justice is not always the most effective or compassionate method of addressing criminal behavior. The author's main objective of this study is to examine the efficiency of restorative justice methods in the criminal justice system in Indonesia. The study adopts a normative juridical research methodology by combining comparative, conceptual, and statutory approaches. The investigation into the effectiveness of restorative justice methods in the Indonesian criminal justice system has generated valuable perspectives on the advantages and hurdles associated with the integration of these methods within the current structure. Research into the effectiveness of restorative justice methods in the context of the Indonesian criminal justice system provides valuable insight into the advantages and barriers associated with the incorporation of these methods into existing structures. The results show that restorative justice provides hope as a replacement for traditional punitive systems, encouraging victim satisfaction, offender responsibility-taking, and decreased recidivism rates. Cases involving restorative justice highlighted the capacity to empower victims, giving them the opportunity to be actively involved in the process and a voice in determining the outcome of their case. Keywords : Criminal Justice; Effectiveness; Restorative Justice.